(untitled) (Homoeopathy for All, 2025)
The World Homoeopathy Day is always a very special occasion for us when we homoeopaths not only celebrate the Birth Anniversary of Dr. Samuel Hahnemann, the visionary whose legacy has shaped our identity and profession. It is a day of connection, offering us the opportunity to reunite with fellow homoeopaths, share cherished memories, and engage in meaningful conversations. The event also features ongoing scientific sessions across various halls, fostering learning, exchange of ideas, and advancement in the field of homoeopathy However, 10th April, 2025, was very special day for me, as we had gathered at Mahatma Mandir, Gandhi Nagar, Gujarat to celebrate this important day. Amidst our usual conversations, I was gently coaxed by Dr. Chaturbhuj Nayak, former Director Central Council for Research in Homoeopathy, to write an article on how I manage to remain joyful, and healthy even at my age of 83-1/2 and a half.